EFEKTIVITAS PELAKSAAN PROGRAM PERLUASAN KESEMPATAN KERJA DI KOTA PEKANBARU - Dalles Siahaan; Zaili Rusli SD (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Unemployment in Indonesia is a difficult problem to eliminate from human life, but the problem of unemployment is not left alone. The high unemployment rate is caused by several factors including the size of the labor force that is not balanced with employment opportunities and the level of education and skills possessed by the people of Indonesia is very low. Pekanbaru City Labor Office implements a program of expanding employment opportunities that is burdened by the Ministry of Manpower of the Republic of Indonesia. The program of expanding employment opportunities implemented by the Pekanbaru City Labor Office is located in Rumbai Subdistrict, because Rumbai Subdistrict is still very minimal and requires the construction of infrastructure or infrastructure facilities and many have unemployed communities that must be empowered. This study provides an overview of community empowerment in reducing the unemployment rate in Pekanbaru city while finding inhibitory factors. Based on the results and discussions of the research can be concluded that the program of expanding employment opportunities is implemented through public services with a budget of the State Budget where the types of activities include labor-intensive infrastructure that aims to seek the expansion of opportunities. This type of research is qualitative research with phenomenological approach. Data collection obtained both primary and secondary data collected through observation interviews and documentation, then analyzed so that it can be drawn conclusions from existing research problems. The result of the study is that the program of expanding employment opportunities is less effective because some indicators of success are not achieved. Inhibitory factors include natural conditions and climate or weather at the time of the implementation of the program so that the program is not carried out properly or not in accordance with the planned time. Keyword : Effectiveness, Program Implementation, Expansion of Employment                    Opportunities